The Contribution of Guidance to English Learning Motivation - Lubis, Fitriadi; Oktapian, Ardi (KnE Social Sciences, 2023)
The purpose of this research is to describe the relationship between learning guidance and learning motivation. This study appliaed descriptive correlational research type. The data was obtained from 75 students as the samples by random sampling technique. The instrument used in this research was questionnaire. The data was analyzed by using SPSS program. The result of this study shows that the correlation between gudance and learning motivation was 0.30. The contribution of guidance was 9% to learning motivation variable. Keywords: English learning; learning guidance; learning motivation